Principles and methods of explainable artificial intelligence in healthcare - Briones, Alfonso Gonzalez; Bhoi, Akash Kumar; Srinivasu, Parvathaneni Naga; Albuquerque, Victor Hugo C De (IGI Global, 2022)
"This book focuses on the Explainable Artificial Intelligence (XAI) for healthcare, providing a broad overview of state-of-art approaches for accurate analysis and diagnosis, and encompassing computational vision processing techniques that handle complex data like physiological information, electronic healthcare records, medical imaging data that assist in earlier prediction.
Includes bibliographical references and index. - Mode of access: World Wide Web
Keywords: Artificial intelligence; DIagnosis -- Data processing